The girl with the dragon tattoo [videorecording (DVD)] - Fincher, David; Plummer, Christopher; Craig, Daniel, 1968-; James, Geraldine, 1950-; Visnjic, Goran, 1972-; Richardson, Joely; Wright, Robin, 1966-; Mara, Rooney; Skarsgård, Stellan; Larsson, Stieg, 1954-2004 (Sony Home Entertainment, 2012)
Hoping to distance himself from the fallout of a libel conviction, journalist Mikael Blomkvist retreats to a remote island in Sweden's far north where the unsolved murder of a young girl still haunts her industrialist uncle forty years later. Ensconced in a cottage on the island where the killer may still roam, Blomkvist's investigation draws him into the secrets and lies of the rich and powerful, and throws him together with one unlikely ally: tattooed, punk hacker, Lisbeth Salander.